Cushing’s syndrome in a young woman due to prolonged betamethasone nasal drop use: a case report - Mohammadsadra Shamohammadi; Delaram Eskandari; Amir Ziaee; Seyed Hossein Samadanifard; Haleh Chehrehgosha; Amir Hossein Ghanooni (Journal of Medical Case Reports)
Abstract Background Cushing’s syndrome is an uncommon but serious condition caused by long-term exposure to elevated cortisol levels, which is usually iatrogenic in origin. Although systemic corticosteroids are the most frequent agents, the association of intranasal corticosteroids with this condition is remarkably rare. Case presentation This report is about a 21-year-old Iranian woman using betamethasone nasal drops for nasal obstruction. The patient presented with weight gain, Amenorrhea, mood disturbances, red purplish striae, and mild hirsutism. Hormonal assessments revealed suppression of the hypothalamic–pituitary–adrenal axis. Conclusion This case demonstrates the underappreciated systemic effects of intranasal betamethasone to induce Cushing’s syndrome. It serves as a pivotal reminder of the need for vigilance in prescribing practices and reinforces the importance of early diagnosis to ensure favorable patient outcomes.